Association between serum vitamin D levels and venous thromboembolism (VTE): A systematic review and meta-analysis of observational studies. (November 2020) - Wan, Jia; Yuan, Jie; Li, Xiaogang; Bao, Yan; Hou, Yi; Li, Zhaoxiang; Tan, Shing Cheng; Low, Teck Yew; Chu, Yan
Highlights: 1-The overall analysis showed a significant increased risk of VTE in subjects with low levels of serum vitamin D compared with those with normal vitamin D levels. 2-In the stratified analysis, low vitamin D levels were positively associated with an increased risk of VTE in prospective population-based studies and in subjects below 60 years old. Abstract: Objective: Although many studies have attempted to unravel the relationship between vitamin D deficiency and the incidence of VTE, the results remained inconsistent. To address this discrepancy, we performed a systematic review and meta-analysis to precisely disentangle the relationship between serum vitamin D levels and VTE risk. Methods: The Web of Science, Scopus, PubMed/Medline, Embase, and Google Scholar databases were searched for all available observational studies that reported the risk of venous thromboembolism (VTE) based on serum vitamin D levels categories. The search was performed up to March 2020. Results: Seven studies were included. The overall analysis showed a significantly increased risk of VTE in subjects with low levels of serum vitamin D compared with those with normal vitamin D levels (RR = 1.34; 95% CI: 1.07–1.69; P = 0.011). In a sensitivity analysis, we did not observe a significant effect of any individual study on the combined effect sizes. Nevertheless, significant heterogeneity was present among the studies (Cochrane Q test, p = 0.018, I 2 = 61%). In the stratified analysis, low vitamin D levels were positively associated with an increased risk of VTE in prospective population-based studies (RR = 1.31; 95% CI: 1.06–1.61; P = 0.010) and in subjects below 60 years old (RR = 1.28; 95% CI: 1.07–1.54; P = 0.060). Conclusion: our systematic review and meta-analysis showed that a low serum vitamin D level was indeed associated with an increased risk of VTE.